Expanding Maternity Waiting Homes as an Approach to Improve Institutional Delivery in Southwest Ethiopia: A Community-Based Case-Control Study - Meaza Hailu; Fikru Tafese; Gebeyehu Tsega; Ayinengida Adamu; Kiddus Yitbarek; Tizta Tilahun; Yibeltal Siraneh; Belay Erchafo; Mirkuzie Woldie (SAGE Publishing, 2021)
With the promising efforts in increasing institutional delivery yet, maternal and child mortality is high in Ethiopia. One of the strategies used to minimize this problem was the introduction of Maternity Waiting Homes (MWH). MWHs are residential facilities for pregnant women near a qualified medical facility. The introduction of MWHs has improved institutional delivery in many countries. In Ethiopia however, the contribution of MWHs was rarely studied. To fill this gap, we have conducted a community-based unmatched case-control study from March 1 to April 20, 2016, in Southwestern Ethiopia. Mothers who delivered at a health facility within 1 year were considered as cases while mothers delivered at home were controls. We used simple random sampling to identify study participants from the pool of cases and controls who were identified by census. Data were analyzed using SPSS Version 20. Binary logistic regression was used to identify significant predictors. A total of 140 cases and 273 controls were included in the study. Among the case, 86 (61.4%) used MWHs during their last delivery. Variables like educational status of the mothers [AOR = 2.96, 95% CI: 1.41, 6.23], educational status of the husband [AOR = 5.19, 95% CI: 1.52, 17.76], and having antenatal care follow up [AOR = 3.22, 95% CI: 1.59, 6.54]. This study remarks, accessing MWHs, creating better awareness in utilizing them, and practicing antenatal follow-up have a crucial role in improving institutional delivery. Therefore, strengthening the existing and establishing new MWHs to deliver quality services is a good strategy in reducing home delivery.